Penguatan Identitas Budaya Siswa Sekolah Dasar Melalui Pembelajaran Berbasis Kearifan Lokal: Kajian Hubungan Manusia, Kebudayaan, Dan Pendidikan Karakter - Mulya Ade Irma Suryani; Eko Handoyo (BEduManagers Journal : Borneo Educational Management and Research Journal, 2026)
The cultural identity crisis among the younger generation, particularly elementary school students, is a serious challenge in the era of globalization, which is increasingly eroding local wisdom values. This article aims to critically examine the relationship between humans, culture, and elementary education, and to analyze the role of local wisdom-based learning in strengthening cultural identity and character development in elementary school students. The method used is a systematic literature study with a descriptive qualitative approach, sourced from indexed national and international journals over the past decade. The results of the study indicate that humans and culture are inseparable entities; culture dialectically shapes human perspectives, values, and behavior. In the context of elementary education, local wisdom, which encompasses the values ​​of mutual cooperation, deliberation, courtesy, tolerance, and responsibility, plays a strategic role in the holistic and contextual formation of student character. Local wisdom-based learning has been proven to strengthen students' socio-cultural identity, increase the relevance of education to real life, and serve as a foundation for authentic character development. This article recommends the systematic integration of local wisdom into the elementary school curriculum as a critical response to cultural homogenization caused by globalization. These findings contribute to the development of an educational approach grounded in the nation's cultural roots.